Screening of refractive errors and ocular disorders of professional soccer players - V. Tavares, Emidio; Apelbaum, Benny; Mendes, Sergio B.; Antonio N. Oliveira, Obidulho; Santos Silva, Paulo; Pedrinelli, Andre; A. Greve, Julia Maria; Hernandez, Arnaldo J.; Marcolino, Bruna A. (Open Science Journal, 2021)
To improve their performance, many athletes already invest a significant amount of time and effort in training camps, personal trainers, and equipment, while neglecting to invest in their vision. However, improving visual performance can help improve overall performance in a way that other training regiments cannot. Even for athletes without vision problems, improving visual performance - such as increasing dynamic visual acuity, decreasing reaction times, and improving eye-hand coordination - is an integral component of improving overall performance. To verify if the changes found in soccer players exceeded the 40% found in the literature. The athletes were all submitted to visual acuity (VA) tests without correction using the Snellen eye chart and the noncontact intraocular pressure (IOP) by means of a computerized tonometer. They also underwent a self-refraction examination through a self-refractor. Among the 54 athletes that presented to the screening (108 eyes) 93/108 (86%) had refractive errors in one or both eyes. In 108 eyes there was 50 (46%) hyperopic eye with astigmatism; 19/108 (18%) of myopic astigmatism, 15/108 (14%) with myopia, 6/108 (6%) with hypermetropy and 15/108 (14%) were emmetropes. The prevalence of refractive errors was hyperopic astigmatism followed by myopic astigmatism (50 vs 19 cases). The left eye was the one that presented more hyperopic and myopic astigmatism in relation to the right eye, 52% and 58%, respectively. There were no differences in mean VA and IOP between in the right and left eyes, respectively. The changes verified in the screening of the present study exceeded 40% of ophthalmological alterations found in soccer players and contemplates the hypothesis of the study.